PENERAPAN MODEL RACI DALAM PENANGANAN MASALAH LAYANAN TEKNOLOGI INFORMASI PADA APLIKASI GRAMEDIA DIGITAL - Fenny Purwani; Erin Aryanti; Resa Ayu Sari; Koiriah Maula Nanda; Dina Olyvia (Jurnal Riset Teknik Komputer, 2025)
Gramedia Digital is a platform that provides electronic book services widely used by the Indonesian public. However, in its operation, users often encounter issues such as frequent application crashes, slow content access, and unresponsive checkout processes. These problems indicate inefficiencies in handling information technology (IT) service incidents. This study aims to apply the RACI model (Responsible, Accountable, Consulted, Informed) to map out the roles and responsibilities of each party involved in the IT service issue resolution process in the Gramedia Digital application. The research method used is descriptive qualitative with a case study approach. The analysis shows that the implementation of the RACI model can clarify task distribution among teams, reduce work duplication, and improve the effectiveness of incident handling. These findings provide recommendations to strengthen the IT service management structure at Gramedia Digital, particularly in the aspect of responding to service disruptions.